Dari Kebutuhan Menjadi Ancaman: Ironi Penduduk Pendatang di Kota Balikpapan 1970 – 2013 - Akhmad R. Pratama (Lembaran Sejarah, 2019)
This article attempts to portray the migration of newcomers into East Kalimantan province during the height of economic growth fostered by the oil and gas and forestry industry. During the decades of 1970-2000, Balikpapan received significant amount of inmigration as a result of labor demand. Since 2010, the municipality had started to apply stringent requirements to immigrants to the city. The dilemma of labor demand and the pressure immigration causes to the needs of the urban citizens has turned this into an irony. On the one hand, the presence of laborers was needed for the petroleum and forestry industry, but on the other hand, their presence has resulted in friction with the local population.